COMMUNITY OF PRACTICE AS ONE OF THE COMPETITIVE ADVANTAGE OF ORGANIZATION - Veronica, Veronica; Suryawan, Angellia Debora (Bina Nusantara University, 2012)
Many organizations in the world realize that to maintain the stability of an organization within a lot of turnover in human resources, Knowledge Management (KM) is a matter that cannot be forgotten. Since by storing the knowledge, organizations can continue to distribute the knowledge to people and to develop it into a practice of learning, problem solving, and then at the end it becomes a â€œBest Practiceâ€. Sharing knowledge becomes the main reference in KM in large and small organizations. By multiplying the activities of knowledge sharing among employees in an organization, it can improve the competitiveness of the organization. All activities in knowledge sharing will be easier if it is formed in a Community of Practice (CoP). CoP can be regarded as a best method. In addition there are many benefits that can be spawned by it, such as in the development, dissemination of knowledge to the development of culture in an organization. The method in this paper uses literature study by describing best practices and case studies in a private bank in Indonesia. By forming the CoP, it is expected to motivate employees to share knowledge for the improvement of organizational performance.Keywords: organization, knowledge management, community of practice